Cluster Preface: Radicals – by Young Chinese Organic Chemists - Zhu, Chen; Liu, Xin-Yuan (Synlett, 2021)
(left) received his B.S. degree from Xiamen University in 2003 under the supervision of Prof. Pei-Qiang Huang, and his Ph.D. degree from the Shanghai Institute of Organic Chemistry in 2008 under the supervision of Prof. Guo-Qiang Lin. After postdoctoral research at Gakushuin University, Japan with Prof. Takahiko Akiyama, he moved to the University of Texas Southwestern Medical Center, working as a postdoctoral fellow with Prof. John R. Falck and Prof. Chuo Chen. He was appointed as a professor at Soochow University, China in December 2013. He is currently the Head of the Organic Chemistry Department at Soochow University. His current research interests include radical-mediated transformations, in particular radical rearrangements, and their applications in the construction of natural products and biologically active compounds. Xin-Yuan Liu (right) obtained his B.S. degree from Anhui Normal University (AHNU) in 2001. He continued his research studies at both the Shanghai Institute of Organic Chemistry (SIOC), CAS and AHNU under the joint supervision of Prof. Dr. Shizheng Zhu and Prof. Dr. Shaowu Wang, obtaining his master’s degree in 2004. After a one-year stint in Prof. Gang Zhao’s laboratory at SIOC, he joined Prof. Dr. Chi-Ming Che’s group at The University of Hong Kong (HKU) and earned his Ph.D. degree in 2010. He subsequently undertook postdoctoral studies in Prof. Che’s group at HKU and in Prof. Carlos F. Barbas III’s group at The Scripps Research Institute. At the end of 2012, he began his independent academic career at the Southern University of Science and Technology (SUSTech) and was promoted to a tenured Full Professor of SUSTech in 2018. His research interests are directed towards the design of novel chiral anionic ligands to solve radical-involved asymmetric reactions.
Keywords: radicals; alkene difunctionalization; photocatalysis; C–H functionalization